Asking the Right Questions: The Role of the Conservator in Digital Projects - Paris, Jan (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2008)
Jan Paris, conservator at the library of the University of North Carolina (Chapel Hill) explains how she decides whether vulnerable material from the special collections may be digitized and under what conditions. She considers not only the condition of the objects, but also the purpose of the digitization process: education, preservation, creating a facsimile edition or as part of a large-scale preservation project. These can be summarized as the impact of preservation considerations such as the reduction in handling, the reduction in the need for interventive conservation and the impact of access considerations such as enabling value-added research, on-demand digitization and producing aids to teaching.